2010
DOI: 10.3892/ol_00000024
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of free vascularised fibula graft and extracorporeally irradiated osteochondral graft for osteosarcoma of the proximal ulna

Abstract: Abstract. the elbow is an uncommon site for malignant bone tumors. surgical options for the reconstruction of the elbow joint are limited and technically challenging. In this study, we describe a patient with osteosarcoma of the proximal ulna treated by wide resection and reconstruction with a combined use of free vascularised fibula graft and extracorporeally irradiated osteochondral graft. ten years after the surgery, the patient is alive, without disease and is able to play golf with no lateral instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Reconstruction after total or partial olecranon involving proximal ulna resections for tumors is challenging. Many reconstructive approaches have been described including radial neck to humeral trochlea [24], free and vascularized fibula autografts [6, 7], combined fibular autograft with osteochondral irradiated graft [13], endoprosthetic reconstruction [810], and medialization of radius to create a single bone forearm [1]. However, each of these is limited by their shortcomings and concerns about their complications, whereas our method of reconstruction using extracorporeal radiation-treated resected segment of tumor bone aims to address most of these issues (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction after total or partial olecranon involving proximal ulna resections for tumors is challenging. Many reconstructive approaches have been described including radial neck to humeral trochlea [24], free and vascularized fibula autografts [6, 7], combined fibular autograft with osteochondral irradiated graft [13], endoprosthetic reconstruction [810], and medialization of radius to create a single bone forearm [1]. However, each of these is limited by their shortcomings and concerns about their complications, whereas our method of reconstruction using extracorporeal radiation-treated resected segment of tumor bone aims to address most of these issues (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This method allows for early mobilization and immediate commencement of adjuvant chemotherapy but has numerous complications, such as infection, stem loosening, and periprosthetic fracture, that can compromise long-term outcome. Except for the demanding surgical technique, this method is not well established in the setting of large proximal ulna defects 10 . Sewell et al 13 reported 4 patients (mean age, 17.5 years) with proximal ulna tumors treated with wide excision and total elbow arthroplasty, achieving good functional result and elbow stability.…”
Section: Discussionmentioning
confidence: 99%
“…Elbow allografts have been also used as an alternative to biologic reconstruction but have been implicated to a high risk of infection and joint degeneration along with other complications, including fracture, instability, and nonunion 10 . Dean et al 2 reported 23 patients treated with allograft reconstruction after massive bone loss at the elbow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvaging the limb following an ulnar tumor resection poses a complex, reconstructive challenge ( 6 , 7 , 9 11 ). Various options have been reported for the reconstruction of the elbow joint following ulnar tumor resections, such as radius neck-to-humerus trochlea transposition, endoprosthetic reconstruction, allografts, vascularized fibular grafts and extracorporeal irradiation ( 6 , 7 , 9 , 10 ). Due to the location of the tumors, previous studies primarily involved reconstructions of partial ulna defects, and the remnant ulna provided the basis for bone grafts or prosthesis implantation.…”
Section: Discussionmentioning
confidence: 99%